A Blood Exosomal miRNA Signature in Acute Respiratory Distress Syndrome - Gilles Parzibut; Monique Henket; Catherine Moermans; Ingrid Struman; Edouard Louis; Edouard Louis; Michel Malaise; Michel Malaise; Renaud Louis; Renaud Louis; Benoît Misset; Makon-Sébastien Njock; et al. (Frontiers in Molecular Biosciences, 2021)
Acute respiratory distress syndrome (ARDS) is a diffuse, acute, inflammatory lung disease characterized by a severe respiratory failure. Recognizing and promptly treating ARDS is critical to combat the high mortality associated with the disease. Despite a significant progress in the treatment of ARDS, our ability to identify early patients and predict outcomes remains limited. The development of novel biomarkers is crucial. In this study, we profiled microRNA (miRNA) expression of plasma-derived exosomes in ARDS disease by small RNA sequencing. Sequencing of 8 ARDS patients and 10 healthy subjects (HSs) allowed to identify 12 differentially expressed exosomal miRNAs (adjusted p < 0.05). Pathway analysis of their predicted targets revealed enrichment in several biological processes in agreement with ARDS pathophysiology, such as inflammation, immune cell activation, and fibrosis. By quantitative RT-PCR, we validated the alteration of nine exosomal miRNAs in an independent cohort of 15 ARDS patients and 20 HSs, among which seven present high capability in discriminating ARDS patients from HSs (area under the curve > 0.8) (miR-130a-3p, miR-221-3p, miR-24-3p, miR-98-3p, Let-7d-3p, miR-1273a, and miR-193a-5p). These findings highlight exosomal miRNA dysregulation in the plasma of ARDS patients which provide promising diagnostic biomarkers and open new perspectives for the development of therapeutics.